Role of SVEP1 in Stroma-Dependent Hematopoiesis In vitro - Tran, Vinson; O’Neill, Helen C. (Frontiers in Cell and Developmental Biology, 2022)
Study of the microenvironment that supports hematopoietic stem cell (HSC) development in vivo is very difficult involving small numbers of interacting cells which are usually not well defined. While much is known about HSC niches located within the bone marrow in terms of contributing cell types and signalling molecules, very little is known about equivalent niches within spleen. Extramedullary hematopoiesis in spleen contributes myeloid cells important in the mobilisation of an immune response. As a result, it is important to develop in vitro models to identify the cells which constitute HSC niches in spleen and to identify the regulatory molecules supporting myeloid cell development. Studies described here document a model system to study the maintenance and differentiation of HSC by splenic stromal cells in vitro. The splenic stromal lines 5G3 and 3B5 differ in hematopoietic support capacity. SVEP1 and IGF2 are molecules of interest specifically expressed by 5G3 stroma. Gene knockdown technology using shRNA plasmids has been used to reduce gene expression in 5G3 and to determine specific effects on myeloid cell development following co-culture with overlaid hematopoietic progenitors in vitro. Knockdown of Svep1 gave specific inhibition of a dendritic cell (DC) population described previously in spleen (L-DC). Knockdown of Igf2 resulted in loss of production of a minor subset of conventional (c)DC. SVEP1 is now considered a marker of mesenchymal stromal cells with osteogenic differentiative capacity reflective of perivascular stromal cells. The power of this in vitro model is evidenced by the fact that it has been used to define SVEP1 as a specific adhesion molecule that regulates the hematopoietic process dependent on stromal niche interaction. The identification of stromal cells and molecules that contribute to the hematopoietic process in spleen, brings us closer to the realm of therapeutically regulating hematopoiesis in vivo, and to inhibiting niches which support cancer stem cells.